ANALISIS DEGRADASI MATERIAL KOMPONEN BOILER DAN PERHITUNGAN SISA UMUR PAKAI BERDASARKAN UJI STRESS RUPTURE - , MUJI PRIHAJATNO; , Mochammad Noer Ilman, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Boiler is a equipment that is used to change water into steam through heat transfer mechanism. The steam is used to drive a turbine. Boiler consists of several components that allows a system to generate power. Boiler components receive a heavy workload in the form of fluid pressure and high temperature. So that it is necessary to evaluate and calculate of remaining life to avoid failure. The evaluate process of boiler components conducted include economizer pipe, waterwall pipe, primary superheater pipe, secondary superheater pipe, and reheater pipe. The method used in the evaluation is experimental with of test and observations. The performed test include is a tensile and hardness test, EDX, X-RD, and weight loss test based on ASTM D-3483. The observation is where a visual and microstructure used to optical microscope and SEM. Whereas the calculation of remaining life is performed by the Larson-Miller parameter from stress rupture testing. The results of this investigation shows that the boiler component materials have degraded. Itâs seen from mechanically occur reduction in hardness and ductility. While visually in wall surfaces pipe occurs pitting corrosion, erosion corrosion, oxidation corrosion. The materials microstructural degradation including spheroidization, graphitization, cavity, decarburizing, and grain-boundary slip. The remaining life of boiler components variously including 142.520 hours of economizer pipes, 168.573 hours of waterwall pipes, 1.172 hours of primary superheater pipes, 1.518 hours of secondary superheater pipes, and 105.713 hours of reheater pipes. The case study of failure the primary superheater pipe occurs because the creep mechanism. The cause of failure due to short-term overheating caused by silica (SiO2) deposite in wall surfaces pipe so inhibits the heat transfer rate.